ESPACIO MENTAL Y LINGÜÍSTICO DEL DISCURSO FILOSÓFICO RELIGIOSO RUSO DEL FIN DEL SIGLO XIX Y PRINCIPIOS DEL SIGLO XX - Kosareva, Larisa; Murashova, Olga; Fisenko, Olga (Revista Inclusiones, 2018)
In article, language of the Russian religious and philosophical discourse of the end XIX– beginning of XX is considered. The originality of the Russian religious Renaissance, which is not either philosophy or literature, is described in traditional understanding. The mythology of a religious and philosophical discourse in which, the myth is way of expression of identity by the writer, his art picture of the world is analyzed. It is proved that the religious and philosophical discourse is a unity of art and philosophical creativity. Forms of representation of a discourse are philosophical poems, philosophical treatises, philosophical dialogues, aphorisms, monographs, articles, etc.